Cinemática e distribuição do gás ionizado na região central das galáxias Seyfert NGC4501 e NGC3982 - Brum, Carine (2015)
We present two-dimensional (2D) maps for emission-line fluxes and ratios and kinematics for the central regions of the Seyfert galaxies NGC 4501 and NGC 3982, from optical spectra obtained with the GMOS (Gemini Multi Object Spectrograph) Integral Field Unit (IFU) at the Gemini North telescope at a spatial resolution of ≈ 50 pc for NGC4501 and ≈30 pc for NGC 3982. This maps were constructed from by fitting the emission-line profiles of Ha, [N II] ll6548,6583, [S II] ll6716,6730 e [O I] l63000 by Gaussian curves. For NGC 4501, we have also obtained measurements for the stellar kinematics by fitting the Na I l5897 °A absorption by stellar templates, using the pPXF method. Such measurements were not possible for NGC3982, due to the nondetection of absorption lines with signal-to-noise ration high enough. NGC 4501 presents extended-line emission to up to 5′′ from the nucleus with flux peak seen at the nucleus. NGC3982 also presents the emission peak at the nucleus for all lines, however it presents emission over the field of view (7′′ × 15′′). A ring of H II regions is observed in the Ha emission with a radius of 5′′ from the nucleus for this galaxy. The gas velocity fields for both galaxies present rotation pattern, being well represented by a kinematic model of rotating disk with circular orbits in the plane of the galaxy. The highest residuals (observed velocities − model) present correlations with dust structures, which can be interpreted as inflows towards the nucleus. The stellar velocity dispersion of the bulge of NGC 4501 is s⋆=150±30 kms−1, resulting in a black hole mass of MBH=3+5 −2 ×107M⊙ based on the M − s relationship. The velocity dispersion map for NGC4501 show values ranging from 50 to 150 kms−1 for the forbidden lines, while the Ha maps shows overall smaller values, with s < 100 kms−1 at all locations. The highest s values for all emission lines are observed at 2-3′′ northeast from the nucleus for NGC 4501, being co-spatial with a distortion seen in the velocity field. In NGC 3982 observed s values ranging 50 to 150 kms−1, with the highest values observed at 1′′ east from the nucleus. The electron density maps obtained from the [S II] l 6716/l6730 line ratio shows values between 100 cm−3 the nucleus to 900 cm−3 in a ring with radius 1′′ for NGC 4501 and values reaching 100 cm−3 to 3000 cm−3 for NGC 3982.